L’ambiguïté de la zone relationnelle dans un collectif de télétravailleuses : une étude de cas dans une agence de placement de personnel - Lucie Enel (Communiquer)
In this study centered around a communicational approach, we investigate the relational issues surrounding the development of a work collective from the experience of teleworkers in an employment agency. To that end, we question the communication practices and relational dynamics of a work team whose members work exclusively remotely. The results show some ambiguity surrounds the relational zone. On one hand, the workers strongly feel that they belong to their team, and even perceive the physical distance as the main factor responsible for good relationship in the team. On the other hand, most of the divergences between workers cannot be revealed. Thus, we argue that physical distance does not dismantle the work collective, but make it exist in a paradox that results from misunderstanding and individual representations, ultimately leading to superficial cohesion.